PROTOZOA USUS SEBAGAI FAKTOR RISIKO MALNUTRISI PADA ANAK SEKOLAH DASAR: TINJAUAN LITERATUR - Husaini Gustiar; Linda Septiani; Betta Kurniawan; Jhons Fatriadi Suwandi (CV. Jasa Sukses Abadi, 2026)
Intestinal protozoal infection is an important health problem among elementary school children, especially in areas with poor sanitation and high population density. Protozoa such as Giardia lamblia, Entamoeba histolytica, Cryptosporidium spp., and Blastocystis hominis can disrupt nutrient absorption, trigger chronic diarrhea, alter gut microbiota composition, and induce mucosal inflammation, which directly affects children’s nutritional status. This literature review aims to analyze the role of protozoal infections as risk factors for malnutrition by examining publications from 2020 to 2025 indexed in PubMed, Google Scholar, and ScienceDirect. The method involved selecting articles based on inclusion criteria, methodological quality, and relevance to nutritional status variables. The analysis showed that the prevalence of protozoal infections in children ranged from 3.2 percent to 62.5 percent, with wide geographic variation. Giardia lamblia was associated with stunting, with odds ratios ranging from 1.8 to 2.4. Cryptosporidium spp. contributed to wasting through recurrent chronic diarrhea. Entamoeba histolytica was related to underweight conditions. Blastocystis hominis played a role in mild nutritional deficits through subclinical inflammation and disruption of microbial balance. Behavioral factors such as lack of handwashing with soap, consumption of untreated water, fecal-oral exposure, and prolonged residence in high-risk environments increased the likelihood of malnutrition. This review concludes that intestinal protozoal infections significantly contribute to malnutrition among elementary school children through impaired absorption, chronic diarrhea, mucosal inflammation, and persistent digestive dysfunction.